2021
DOI: 10.3390/cells10051238
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Aging Affect Liver Sulfur Metabolism in Rats

Abstract: Hypertension and age are key risk factors for cardiovascular morbidity and mortality. Hydrogen sulfide (H2S), a gaseous transmitter, contributes significantly to regulating arterial blood pressure and aging processes. This study evaluated the effects of hypertension and aging on the hepatic metabolism of sulfur-containing compounds, the activity of the enzymes involved in sulfur homeostasis, and the liver’s ability to generate H2S. Livers isolated from 16- and 60-week-old normotensive Wistar Kyoto rats (WKY) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…But a study shows the effect of aging on rat liver and the regulation of sulfur compounds. This study concludes that there is a mixed trend observed in the production of sulfur compounds with aging 36 .…”
Section: Methodsmentioning
confidence: 57%
“…But a study shows the effect of aging on rat liver and the regulation of sulfur compounds. This study concludes that there is a mixed trend observed in the production of sulfur compounds with aging 36 .…”
Section: Methodsmentioning
confidence: 57%
“…EMVs were more effective than EEXs on regulating GSSG and klotho. MDA and GSSG have been implicated in aging and served as oxidative stress markers, and high levels of MDA and GSSG were found in the hippocampus of aged rat [36, 37]. Klotho gene is widely accepted as an anti-aging gene with anti-oxidative stress and anti-inflammation functions, and klotho overexpression could extend life span of mice [38].…”
Section: Discussionmentioning
confidence: 99%
“…Aging associated biomarkers including MDA, GSSG and klotho levels were detected according to the manufacturer’s instructions (MDA: Beyotime, cat# S0131M, GSSG: Beyotime, cat# S0053, Klotho: ZCI Bio, cat# ZC-31968) as previously reported, and TERT level was measured by q-PCR [36, 37, 39, 40]. The detailed procedures could be found in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in cellular metabolism play an important role in controlling and steering the inflammatory state of both endothelial cells and immune cells, and this change has been shown to be related to hypertension in multiple studies. [85][86][87] Many studies have demonstrated the brain-gut connection pathway of hypertension, but relatively little is known about the role of gut-kidney connection, in particular, whether changes in renal function are associated with increased intestinal permeability and changes in the expression of inflammatory genes. Our results present candidate pathways and genes to explore the relationship between metabolism, inflammation, and hypertension on the gut-kidney axis.…”
Section: Discussionmentioning
confidence: 99%